THE HOUSE, THE HOME AND THE FAMILY IN CAMPO DE MONTI THE IN THE XVIII CENTURY - Hernández López, Carmen (Revista de Historia Social y de las Mentalidades, 2011)
We are planning the study of the Antique Regime soc iety based on the house, understanding it like an element of rural arquitect ure and the material culture, like a domestic space and production centre, consume and s ocial reproduction. Begining the investigation with El Bonillo village we pretend to show that the house and the family as associative structures are the ones that explain the social organization and the diferents ways of life. Definetly we pretend to und erstand how they reproduce and get the great differences that take part in the rural zone.